Effects of magnesium supplementation on carotid intima–media thickness and metabolic profiles in diabetic haemodialysis patients: a randomised, double-blind, placebo-controlled trial. Issue 7 (11th February 2019) - Talari, Hamid Reza; Zakizade, Mehrafrouz; Soleimani, Alireza; Bahmani, Fereshteh; Ghaderi, Amir; Mirhosseini, Naghmeh; Eslahi, Masoumeh; Babadi, Mahtab; Mansournia, Mohammad Ali; Asemi, Zatollah
Abstract: This study evaluated the effects of Mg administration on carotid intima–media thickness (CIMT), glycaemic control and markers of cardio-metabolic risk in diabetic haemodialysis (HD) patients. This randomised, double-blind, placebo-controlled clinical trial was conducted in fifty-four diabetic HD patients. Participants were randomly divided into two groups to take either 250 mg/d Mg as magnesium oxide ( n 27) or placebo ( n 27) for 24 weeks. Mg supplementation resulted in a significant reduction in mean ( P <0·001) and maximum levels of left CIMT ( P =0·02) and mean levels of right CIMT ( P =0·004) compared with the placebo. In addition, taking Mg supplements significantly reduced serum insulin levels ( β =–9·42 pmol/l; 95% CI –14·94, –3·90; P =0·001), homoeostasis model of assessment-insulin resistance ( β =–0·56; 95 % CI –0·89, –0·24; P =0·001) and HbA1c ( β =–0·74 %; 95 % CI –1·10, –0·39; P <0·001) and significantly increased the quantitative insulin sensitivity check index ( β =0·008; 95 % CI 0·002, 0·01; P =0·002) compared with the placebo. In addition, Mg administration led to a significant reduction in serum total cholesterol ( β =–0·30 mmol/l; 95% CI –0·56, –0·04; P =0·02), LDL-cholesterol ( β =–0·29 mmol/l; 95% CI –0·52, –0·05; P =0·01), high-sensitivity C-reactive protein (hs-CRP) ( P <0·001) and plasma malondialdehyde (MDA) ( P =0·04) and a significant rise in plasma total antioxidant capacity (TAC) levels ( P <0·001) compared with the placebo. Overall, we found that taking Mg for 24 weeks by diabetic HD patients significantly improved mean and maximum levels of left and mean levels of right CIMT, insulin metabolism, HbA1c, total cholesterol and LDL-cholesterol, hs-CRP, TAC and MDA levels.